"Some of Us Pushed Forward and Let the World See What Could Be Done": Aboriginal Australian Nurses and Midwives, 1900–2005. (1st November 2016) - Best, Odette; Gorman, Don
Abstract : This paper locates the voices of Aboriginal nurses and midwives which only emerged in publications from the 1950s onwards. It seeks to privilege the voices of Aboriginal nurses and midwives, and recognise their contributions to the nursing and midwifery professions. It identifies two key developments in Australian history that influenced the acceptance of Aboriginal people into a career in nursing and midwifery: the gradual decline of policies of protection, segregation and assimilation, and the shift of nursing education from hospitals into the tertiary sector. The authors identify four key themes that emerge from this review of Aboriginal nurses' publications: (1) the ongoing experience of racism faced by Aboriginal nurses and midwives, which was first reported in the 1950s and continues to be reported today; (2) the desire of Aboriginal nurses and midwives to work in their communities and contribute to improving the health of Aboriginal people; (3) the call for improved education about Aboriginal health issues as part of the broad nursing curriculum; and (4) the value of targeted strategies to recruit and retain Aboriginal nursing students.